(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
The tracking of public spending on education has gradually become a fashionable practice because of the general view that public expenditure may not reach the publicly run schools due to leakages triggered by corruption, mismanagement and weak monitoring mechanisms. This has increased the fear that the expenditure on primary education might not translate into improved learning. Consequently, this research tracked the flow of instructional materials from the Federal Government Agency through the State Government Agency and the Local Government Agency to the primary school level, assessed the efficiency of public spending and determined the location and scale of anomaly by adopting Public Expenditure Tracking Survey (PETS) to address issues of public accountability in the management of the Universal Basic Education funds in Oyo state. Descriptive survey research design was adopted for the study using the quantitative and qualitative multi-angular data collection strategy which blended primary survey-based data with secondary information from documentary sources. The population of the study consisted of all seventy four (74) primary schools in Ibadan North Local Government area of Oyo State, Nigeria. The results indicated a significant evidence of resource leakage, existence of lobbying, hoarding of textbooks by some schools and lack of information to the stakeholders on funds released and allocation to schools. Based on the findings, the study recommended that necessary information on public allocations be made readily available to all stakeholders and that policy reforms be made to improve and enforce public accountability in the process of basic education delivery especially in Oyo State, Nigeria.